Dysphagia in cervical spinal cord injury: How international literature trends can guide South African practice patterns - A scoping review - Kim A. Coutts (AOSIS, 2021)
Background: The limited data regarding dysphagia in high-level spinal cord injuries (SCIs) stem from economically developed countries. Dysphagia is prevalent in patients with cervical SCI; however, in a South African context, speech-language pathologists (SLPs) are not seen as key when managing this population. This may result in patients not being screened or identified early, leading to possible complications. The literature could provide useful insight on how best to address this clinical gap. Objectives: The aim of my study was to conduct a scoping review on the description of dysphagia, the risk factors for developing dysphagia post-SCI and the practice patterns of team members working with dysphagia in cervical SCIs. Methods: A five-step scoping review was undertaken. Data were analysed by using descriptive statistics as well as a thematic analysis by using a top-down approach. Results: Through the process of screening according to the inclusion and exclusion criteria, 25 articles were included. Primarily, the pharyngeal phase was affected, which can lead to an aspiration pneumonia. The key risk factors were the presence of a tracheostomy tube, the use of ventilation and anterior spinal cord surgery. There was little mention regarding specific practice patterns, but an interdisciplinary approach was suggested as the most efficient model. Conclusions: Specific guidelines and management options need to be considered for a South African context, given the high incidence of trauma-related injuries. There needs to be locally produced research, providing suggestions on how different team members can screen and identify dysphagia within this population. Solutions need to be unique, and contextually responsive and appropriate. Clinical implications: The team members and the roles of these different team members need to be re-examined in order to ensure the early identification and management of cervical SCI patients who are at risk of developing a dysphagia.